2011
DOI: 10.1016/j.jacc.2011.02.023
|View full text |Cite
|
Sign up to set email alerts
|

2-Year Follow-Up of a Randomized Controlled Trial of Everolimus- and Paclitaxel-Eluting Stents for Coronary Revascularization in Daily Practice

Abstract: The substantial clinical benefit of the EES over the PES with regard to measures of both safety and efficacy is maintained at 2 years in real-life practice with an increasing benefit in terms of safety and efficacy between 1 year and 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(44 citation statements)
references
References 12 publications
3
40
1
Order By: Relevance
“…25 Compared with PES, the overall risk of definite ST was lowered by 63% with the use of EES, whereas the risk of VLST was lowered by 77% between 1 and 2 years of follow-up. In the randomized Clinical Evaluation of the XIENCE V Everolimus Eluting Coronary Stent System in the Treatment of Subjects With De Novo Native Coronary Artery Lesions (SPIRIT) IV trial comparing EES with PES, the overall risk of definite ST at 2 years was also lowered by 64% in favor of EES, whereas the risk of VLST was nonsignificantly reduced by 24% during the very late period (Ͼ1 year).…”
Section: Discussionmentioning
confidence: 90%
“…25 Compared with PES, the overall risk of definite ST was lowered by 63% with the use of EES, whereas the risk of VLST was lowered by 77% between 1 and 2 years of follow-up. In the randomized Clinical Evaluation of the XIENCE V Everolimus Eluting Coronary Stent System in the Treatment of Subjects With De Novo Native Coronary Artery Lesions (SPIRIT) IV trial comparing EES with PES, the overall risk of definite ST at 2 years was also lowered by 64% in favor of EES, whereas the risk of VLST was nonsignificantly reduced by 24% during the very late period (Ͼ1 year).…”
Section: Discussionmentioning
confidence: 90%
“…12 Secondgeneration DESs are expected to overcome these limitations 13 Furthermore, recent reports from observational studies and meta-analyses suggested that the use of EES rather than SES (another first-generation DES) reduces the risk of VLST and repeat revascularization. [4][5][6][7]14,15 However, these results should be interpreted carefully because the results came from observational studies using historical control or from meta-analyses that incorporate indirect comparison or include limited data >1 year.…”
Section: Discussionmentioning
confidence: 99%
“…
I n percutaneous coronary interventions, drug-eluting stents (DESs) have reduced the risk of restenosis and repeat revascularization compared with bare-metal stents.1-3 The secondgeneration DESs with thinner stent struts 4,5 have improved safety and efficacy compared with the first-generation DESs [6][7][8] and has been associated with a reduced risk of late stent thrombosis. 6,8,9 The persistence of polymer material on first-and second-generation DESs after completion of drug release has been Background-Coronary drug-eluting stents with biodegradable polymers have been designed to improve safety and efficacy.
Methods and Results-The Scandinavian Organization for Randomized Trials With Clinical Outcome (SORT OUT)

VII trial-a large-scale registry-based randomized, multicenter, single-blind, 2-arm, noninferiority trial-compared 2 biodegradable polymer drug-eluting stents: the thin-strut cobalt-chromium sirolimus-eluting Orsiro stent and the stainless steel biolimus-eluting Nobori stent in an all-comer patient population.

…”
mentioning
confidence: 99%
“…6,8,9 The persistence of polymer material on first-and second-generation DESs after completion of drug release has been Background-Coronary drug-eluting stents with biodegradable polymers have been designed to improve safety and efficacy. …”
mentioning
confidence: 99%
See 1 more Smart Citation